2022
DOI: 10.1093/icesjms/fsac127
|View full text |Cite
|
Sign up to set email alerts
|

Migration patterns of Greenland halibut in the North Atlantic revealed by a compiled mark–recapture dataset

Abstract: Marine fisheries are often allocated to stocks that reflect pragmatic considerations and may not represent the species’ spatial population structure, increasing the risk of mismanagement and unsustainable harvesting. Here we compile mark–recapture data collected across the North Atlantic to gain insight into the spatial population structure of Greenland halibut (Reinhardtius hippoglossoides), an issue that has been unresolved for decades. The dataset contains 168130 fish tagged from 1952 to 2021, with 5466 (3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…Describes two major populations in the North Atlantic, merging the West Greenlandic and Canadian eastern Arctic, Iceland, and Southeast Greenland regions in a unique population separated from the Norwegian slope. Although this hypothesis is less supported than the previous one, tagging studies also found migrations between NWAS and WNS (Boje, 2002;Vihtakari et al, 2022). For each hypothesized population, equal (all populations follow the same growth rate) and unique (separated growth rate across populations) population growth rates (u) were tested.…”
Section: Tested Modelsmentioning
confidence: 97%
See 2 more Smart Citations
“…Describes two major populations in the North Atlantic, merging the West Greenlandic and Canadian eastern Arctic, Iceland, and Southeast Greenland regions in a unique population separated from the Norwegian slope. Although this hypothesis is less supported than the previous one, tagging studies also found migrations between NWAS and WNS (Boje, 2002;Vihtakari et al, 2022). For each hypothesized population, equal (all populations follow the same growth rate) and unique (separated growth rate across populations) population growth rates (u) were tested.…”
Section: Tested Modelsmentioning
confidence: 97%
“…North Atlantic Oscillation (NAO) index: The NAO is a cyclical climate oscillation, measured as the difference in atmospheric pressure between the Icelandic low and Azores high (Figure 3). This index has been used by Albert and Høines (2003) Survey index maps were created using the ggOceanMaps package (Vihtakari, 2022), with land polygons from Natural Earth Data (https://www.natur alear thdata.com/) and depth polygons from the ETOPO 1 arc-minute bathymetry grid (Amante & Eakins, 2009).…”
Section: Covariatesmentioning
confidence: 99%
See 1 more Smart Citation
“…data) the higher relative read counts were most likely not caused by spawning events, but rather by migration of Greenland halibut into the southern branch. Indeed, the entire stock of Greenland halibut in the Icefjord and other coastal Greenlandic areas results from the immigration of larvae and juveniles from offshore spawning sites in the Davis Strait (Vihtakari et al 2022). In many Greenland fjords, the large adult fishes are thought to be non-spawning expatriates, 'trapped' in the fjords due to the shallow fjord entrance sills (Boje 1994).…”
Section: Distribution Of Species; Spatial and Temporal Differencesmentioning
confidence: 99%
“…Greenland halibut is an important commercial flatfish species in the Arctic that is highly mobile. See Hussey et al (2017); Barkley et al (2018), and Vihtakari et al (2022) for studies of their inter‐regional migration behavior. Age determination is problematic for Greenland halibut; therefore, we focus on mature‐at‐length data.…”
Section: Introductionmentioning
confidence: 99%